Beyond Profitability: Do Sharia and Financial Performance Drive Islamic Bank Value? - Alisha Dwi Fatika; Laila Masruro Pimada (Faculty of Economics UIN Maulana Malik Ibrahim Malang, 2025)
This study aims to examine the effect of financial performance and the Maqashid Sharia Index (MSI) on firm value in Indonesia’s Islamic Commercial Banks (BUS). Financial performance is measured using the Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), Return on Asset (ROA), and Non-Performing Financing (NPF) based on the Capital, Assets, Management, Earnings, and Liquidity (CAMEL) framework. At the same time, firm value is proxied by Economic Value Added (EVA). The study employs panel data from 10 BUS over the 2018–2022 period and applies panel regression analysis. The results indicate that ROA has a significant positive effect on firm value, whereas CAR and FDR have significant negative effects. NPF and MSI show negative but insignificant influences on firm value. These findings suggest that profitability remains the primary determinant of value creation, while Sharia-based performance has not yet contributed significantly to financial value enhancement. The study implies that Islamic banks should prioritise profitability and prudent liquidity management to strengthen firm value. This research is limited by its five-year observation period and the availability of secondary data from 10 banks.